Experimental Study on Pyrolysis of Non-Metallic Materials Separated from Printed Circuit Board Waste via TGA and Analytical Vacuum Fast Pyrolysis of Non-Metallic Fraction of Printed Circuit Board Waste after Copper Separation - Songpol Boonsawat; Qiming Jimmy Yu; Erik L.J. Bohez; Soon Chia (The Global Environmental Engineers, 2019)
In just over half a century electronic equipment and products have revolutionized human lifestyle. At the product’s end of life, e-waste, its components material and other materials have influenced and infiltrated environment in every part of globe. The hazardous effect of plastic materials and debris to biodiversity is well established, but mitigation and planning are often hampered by lack of quantitative data on waste accumulation patterns in landfill. Here we document a study on the pyrolysis of non-metallic material of printed circuit board, the basic elemental part of electronic waste. The non-metallic material is separated from printed circuit board waste during the copper separation processes and was found in powder form at average size up to 177 μm. The purpose of this study is to experimentally investigate the pyrolysis behavior of the non metallic material of printed circuit boards (PCB) waste fraction at a temperature range of 300 ◦C to 600 ◦C by means of the Thermogravimetric Analysis (TGA) and seek to find out the effective pyrolysis temperature that could be used in pyrolysis process in production scale. The experimental results reveal that the chemical composition of the PCB reflects that the main decomposition of PCBs occurs between 250 ◦C and 450 ◦C, and effectively decomposed at 403 ◦C. The pyrolysis of PCBs showed a varying production of aromatic compounds such as phenol, bromophenol, styrene, methylstyrene, and bisphenol A as well as non-aromatic compounds such as acetone and bromomethane, which are strongly related with the initial chemical composition of PCBs.